2016
DOI: 10.1128/jvi.01786-15
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Broad-Based Immunity and Protective Efficacy by Self-amplifying mRNA Vaccines Encoding Influenza Virus Hemagglutinin

Abstract: Seasonal influenza is a vaccine-preventable disease that remains a major health problem worldwide, especially in immunocompromised populations. The impact of influenza disease is even greater when strains drift, and influenza pandemics can result when animal-derived influenza virus strains combine with seasonal strains. In this study, we used the SAM technology and characterized the immunogenicity and efficacy of a self-amplifying mRNA expressing influenza virus hemagglutinin ( IMPORTANCEIn this study, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 83 publications
(86 reference statements)
6
130
0
3
Order By: Relevance
“…HAI titers were low but measurable for the 15-μg dose (two of six responders) and at the 45-μg dose (three of six responders) after a single immunization. Following a boost, titers were measurable in all animals and provided protection to a homologous challenge strain 45 . In another study, mice singly immunized against H1N1 (A/WSN/33), receiving a self-amplifying mRNA, showed no IgG responses after 7 days.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…HAI titers were low but measurable for the 15-μg dose (two of six responders) and at the 45-μg dose (three of six responders) after a single immunization. Following a boost, titers were measurable in all animals and provided protection to a homologous challenge strain 45 . In another study, mice singly immunized against H1N1 (A/WSN/33), receiving a self-amplifying mRNA, showed no IgG responses after 7 days.…”
Section: Discussionmentioning
confidence: 97%
“…Unmodified, sequence-optimized mRNA was used to generate H1-specific responses in mice, ferrets, and pigs at dose levels ∼4- to 8-fold higher than tested by us 20 . Brazzoli et al 45 . evaluated a self-amplifying mRNA that expressed H1 HA from the 2009 pandemic formulated with a cationic nanoemulsion in ferrets.…”
Section: Discussionmentioning
confidence: 99%
“…As little as 100 ng of an RNA replicon vaccine encoding RSV F, complexed to LNP, resulted in potent T and B cell immune responses in mice, and 1 μg elicited protective immune responses against RSV infection in a cotton rat intranasal challenge system 19 . SAM vaccines encoding influenza virus antigens in LNPs or an oil-in-water cationic nanoemulsion induced potent immune responses in ferrets and conferred protection from homologous and heterologous viral challenge in mice 9496 . Further studies demonstrated the immunogenicity of this vaccine platform against diverse viruses in multiple species, including human cytomegalovirus (CMV), hepatitis C virus and rabies virus in mice, HIV-1 in rabbits, and HIV-1 and human CMV in rhesus macaques 50,87,97 .…”
Section: Mrna Vaccines Against Infectious Diseasesmentioning
confidence: 99%
“…An early study demonstrated that a dose as low as 0.1 μg of SAM vaccine encoding respiratory syncytial virus fusion glycoprotein (RSV-F) in an LNP delivery system produced effective cellular and humoral immune responses in mice, and 1 μg elicited potent immune responses and conferred protection from further RSV infections in cotton rats [142]. Immunization with SAM vaccines encoding influenza virus hemagglutinin (HA) in a cationic nanoemulsion protected mice from influenza virus challenges [143, 144]. In other studies, SAM vaccines encoding influenza antigens were successfully delivered to DCs by chitosan-nanoparticles and PEI-based polyplexes, which were also reported to successfully induce humoral and cellular immune responses in mice [145, 146].…”
Section: Biomedical Applicationsmentioning
confidence: 99%